ARTISTIC AND METHODOLOGICAL SIGNIFICANCE OF CELESTIAL BODIES IN CHULPAN POEMS (British Journal of Global Ecology and Sustainable Development, 2023)
This article covers what artistic and methodological aspect the Moon, Star, Solar bodies most common in Chulpan poems have acquired.